Colossians and Philemon : An Introduction and Commentary - Thompson, Alan J. (Downers Grove.: : IVP Academic, 2022)
Paul s letters to the Colossians and Philemon are both brief, but full of theological riches. In the letter to the Colossians, he points us to the sufficiency of Christ for all our needs and shows how us how we must reflect Christ s character in all our relationships. In Philemon we see the power of the gospel to liberate captives, of sin and circumstance, to a new way of living in Christ. In this comprehensive introduction and commentary to both letters, Alan Thompson explores how these letters still have much to teach Christians in the twenty-first century. With astute understanding, he shows how Colossians and Philemon unpack and apply the beauty of the gospel of God s grace and Christ s supremacy. A new volume in the Tyndale New Testament commentary series, Colossians and Philemon: An Introduction and Commentary examines the text section-by-section exploring the context in which it was written, providing thoughtful commentary on the letters to the Colossians and to Philemon, and then unpacking their theology. It will leave you with a thorough understanding of the content and structure of Paul s writing, as well as its meaning and continued relevance for Christians today. The Tyndale New Testament Commentaries are ideal bible commentaries for students and teachers of theology, as well as being usable for preachers and individual Christians looking to delve deeper into the riches of Scripture and discover its meaning for today. With clarity and comprehensiveness, Alan Thompson s commentary on Colossians and Philemon is a brilliant introduction that will give you a renewed appreciation for these two significant letters and a greater understanding of how Christians today can learn from them.